Granulomatous mastitis-a challenging surgical entity - P. B., Thrishuli; B., Akshata Kamath (International Surgery Journal, 2017)
Background: Idiopathic granulomatous mastitis is a rare benign breast disease, first described by Kessler and Wolloch in 1972. It is characterized by chronic necrotizing granulomatous lobulitis of unknown aetiology. The objective of the study is to find out the clinical and management profile of granulomatous mastitis (GM). This study was carried out at JSS hospital, Mysore, Karnataka, India during the period 2014-2016. Methods: Histopathologically diagnosed cases of GM were studied. Data included, detailed history, examination, clinical diagnosis, ultrasound, mammogram and fine needle aspiration cytology (FNAC). All patients were followed for a period of 6 months. Recurrent cases were managed by wide excision and followed for another period of 6 months. Results: 8 patients who were hisptopathologically diagnosed to have granulomatous mastitis were studied. The mean age was found to be 43.5 years. All patients presented with a painless breast lump and were unilateral. The incidence of the same was found to be higher (3.7%) compared to other large volume studies. The best treatment modality with least recurrence in 4 cases was wide local excision and 1 case of quandrantectomy. Conclusions: GM is an uncommon chronic inflammatory disease of the breast. Usually involving a single non-lactating breast in reproductive age group. It clinically mimics tuberculosis and carcinoma. Mammography remains non-conclusive. Excision and wide excision biopsy are both diagnostic and therapeutic in majority of cases. Treatment includes short course of steroids and antibiotic along with close regular surveillance.